2018
DOI: 10.1080/01676830.2018.1513537
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler imaging of orbital vasculature before and after orbital decompression in thyroid eye disease

Abstract: Orbital decompression procedure led to a significant reduction of RI in both CRA and OA in patients with TED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Changes in orbital blood flow in patients with TED have been reported in previous studies ( 9 11 , 22 24 ). Using color Doppler sonography, Somer et al ( 23 ) reported lower mean superior ophthalmic vein blood flow velocity in patients with TED compared with those without TED.…”
Section: Discussionsupporting
confidence: 77%
“…Changes in orbital blood flow in patients with TED have been reported in previous studies ( 9 11 , 22 24 ). Using color Doppler sonography, Somer et al ( 23 ) reported lower mean superior ophthalmic vein blood flow velocity in patients with TED compared with those without TED.…”
Section: Discussionsupporting
confidence: 77%
“…TAO is a common orbital disorder that can lead to dysthyroid optic neuropathy (DON) by compression of the optic nerve by congested tissues and extraocular muscles. The role of vascular blood flow in the pathogenesis of optic neuropathy has been widely investigated with several methods; different studies with Doppler ultrasonography have demonstrated that increase in intra-orbital pressure in TAO patients leads to severe stasis in the superior ophthalmic vein [ 11 13 ]; also, other studies observed an increased resistance in ophthalmic artery and in central retinal artery in TAO patients, which decreases after orbital decompression [ 14 , 15 ]. Some studies with OCTA observed a reduction in macular density in patients with active and inactive TAO [ 16 ], other studies observed a greater macular density in inactive TAO patients [ 17 ] and other studies showed an increase in macular density in active TAO patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We postulate ophthalmologic improvement may have occurred through bone removal adjacent to the medial cavernous sinus and optic canal, relieving compression of the abducens nerve and/or its microvasculature. 5 Decompression may additionally have altered flow and turbulence within the cavernous sinus, allowing self-thrombosis of the fistulous vessels. An additional possibility is that auto-thrombosis occurred with watchful waiting in the absence of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%